A2 Adenosine Receptor Subtypes Overproduction in Atria of Perioperative Atrial Fibrillation Patients Undergoing Cardiac Surgery: A Pilot Study - Maille, Baptiste; Fromonot, Julien; Guiol, Claire; Marlinge, Marion; Baptiste, Florian; Lim, Suzy; Colombani, Charlotte; Chaptal, Marie Charlotte; Chefrour, Mohamed; Gastaldi, Marguerite; Franceschi, Frederic; Deharo, Jean-Claude; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Although atrial fibrillation (AF) is a common cardiac arrhythmia in human, the mechanism that leads to the onset of AF is poorly elucidated. Adenosine is suspected to be implicated in the trigger of AF through the activation of its membrane receptors, mainly A1R and A2R subtypes. Here, we compare blood adenosine concentration (BAC), and A1R, A2AR, A2BR production in right (RA) and left atrium (LA), and on peripheral blood mononuclear cells (PBMCs) in patients with underlying structural heart disease undergoing cardiac surgery with or without peri-operative AF (PeOpAF). Methods 39 patients (30 males and 9 females, mean age, range 65[40-82] years) undergoing cardiac surgery and twenty healthy (8 women and 12 men; 60 [39–72] years) as controls were included. Among patients, 15 exhibited PeOpAF. Results BAC was higher in patients with PeOpAF than others. A2AR and A2BR production was higher in PBMCs of patients compared with controls and was higher in PeOpAF patients than other patients. In LA and RA, the production of A2AR and A2BR was higher in patients with PeOpAF than in other patients. Both A2AR and A2BR production were higher in LA vs RA. A1R production was unchanged in all situations. Finally, we observed a correlation between A1R, A2AR and A2BR production evaluated on PBMCs and those evaluated in LA and RA. Conclusions PeOpAF is associated with high BAC and high A2AR and A2BR expression, especially in the LA, after cardiac surgery in patients with underlying structural heart disease. Whether these increases favor the triggering of AF in this patient population needs further investigation.